The Penyengat School: A Review of the Intellectual Tradition in the Malay-Riau Kingdom - Alimuddin Hassan Palawa (Studia Islamika, 2003)
The articles in al-Imam strongly influenced its readers not only in Riau, but also in Minangkabau and Malaysia. In response to the cultural background of the traditionalist and conservative Malay community, the magazine voiced the spirit of Islamic reform. For example, one of its contributors, ai-Hadi, stressed the urgency of education and reform for the Malay community, and fought strongly for practices not regarded as everyday Islam. Due to its broad reaching influence, the magazine played a pivotal role in the realization and continuation of religious and intellectual reform in Indonesia.DOI: 10.15408/sdi.v10i3.624